STUDIES ON LYMPHOID TISSUE ABSCESSES IN CAMELS (Camelus dromedarius) SLAUGHTERED AT NYALA SLAUGHTERHOUSE, SOUTH DARFOUR STATE, SUDAN. - Aljameel,; .Halima, M.A; El-Eragi, M.O.,; M. S, A.; Asil, ElTigani (Journal of Veterinary Medicine and Animal Production, 2022)
This study was carried out at Nyala slaughterhouse South Darfur State, Sudan to determine the prevalence of abscesses in lymph nodes and spleen and identify bacterial species involved in .A total of 786 slaughtered camels were inspected from 2009 to 2011. 92 camels exhibited 103 abscesses with prevalence rate of 12% (more than one abscesses in some camels).Specimens from these abscesses; 90 in lymph nodes and 13 in spleens were obtained for bacterial isolation and histopathological examination.. Growth was observed in 86 of the specimens. A total of 119 bacterial species was isolated and identified as Corynebacterium spp. (42.9%), Staphylococcus spp. (20.2%), Arcanobacterium spp. (11.8%), Streptococcus spp. (5.1%), Pseudomonas aeruginosa (4.2%), Micrococcus luteus (2.5%), Bacillus spp. (2.5%), Enterobacter spp. (2.5%), Proteus spp. (2.5%), Rhodococcus equi (1.7%), Citrobacter rodentium (1.7%), Enterococcus durans (0.8%), Escherichia coli (0.8%), and Actinobacillus lignieresii (0.8%). Small necrotic abscesses were seen in most histopathological sections of lymph nodes with infiltration of inflammatory cells. Other sections showed depletion of lymphocytic cells (white pulp), and hyperplasia and hypotrophy of blood vessels were also seen. Moreover, amass of thin-walled blood vessels filled with blood and separated by courageous stroma and surrounded by fibrous tissues. Our findings indicate that abscesses in lymph nodes were caused by Corynebacterium pseudotuberculosis, Staphylococcus aureus, Arcanobacterium pyogenes, and Corynebacterium ulcerans, whereas splenic abscesses were caused by S. aureus, A. pyogenes, C. pseudotuberculosis, Streptococcus pyogenes and Ps. aeruginosa. Therefore, Corynebacterium ulcerans, Arcanobacterium pyogenes, Rhodococcus equi and Streptococcus ubaris were first reporting in The Sudan as camel lymphoid tissue pathogens